Pengelolaan Gangren Kaki Diabetik - Ronald W. Kartika (Cermin Dunia Kedokteran, 2017)
Diabetes Mellitus adalah kondisi seumur hidup yang merupakan salah satu penyebab utama kematian di dunia. Hingga 15 % pasien diabetes mellitus akan menderita ulkus kaki diabetik. Pasien ulkus di kaki berisiko tinggi untuk amputasi dan kematian. Pengenalan dini melalui skrining penting untuk mengurangi morbiditas dan mortalitas. Pendekatan interprofessional (dokter, perawat, dan spesialis perawatan kaki) sering diperlukan untuk mendukung kebutuhan pasien.Diabetes Mellitus is a serious, life-long condition which is one of the leading cause of death in the world. Up to 15% diabetes mellitus patients will develop diabetic foot ulcers with increased risk of amputation and mortality. The risk of diabetic foot can be identified with a simplified screening, and subsequent foot ulcers can be prevented. Early recognition of the high-risk foot and timely treatment will save legs and improve patients’ quality of life. An interprofessional approach (physicians, nurses, and foot care specialists) is needed to support patients’ needs.